NILAI SYARI’AH DALAM NOVEL DI ATAS SAJADAH CINTA KARYA HABIBURRAHMAN EL-SHIRAZY (SEMIOTIK) - Sari Devi, Mutia (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Literary works, especially novels, are a very important medium of learning for readers. This is what drives the researcher to study Habiburrahman El-Shirazy's novel Di Atas Sajadah Cinta, as it contains religious values that need to be explored and discussed in detail. This research aims to identify the Sharia values in the novel Di Atas Sajadah Cinta by Habiburrahman El-Shirazy using Charles Sanders Peirce's semiotic approach, which involves the triadic relationship of sign, object, and interpretant. The method used in this research falls under descriptive qualitative research with a library technique by repeatedly reading the text. The results of the research reveal that all Sharia values are categorized into four aspects, including worship in verbal form, such as reciting the Quran, performing dhikr, tasbih, tahlil, and istighfar. Worship in physical acts, such as performing dhuha prayers, the five daily prayers, and tahajjud prayers. Additionally, worship through self-restraint, such as fasting.